Effectiveness of forceps delivery in modern day obstetrics - Pitale, Devdatt Laxman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: There has been an alarming rise in number of caesarean sections all over the world. Instrumental delivery plays an important role to reduce this trend globally. Forceps delivery though proper training and expertise can definitely reduce the rising caesarean section rates in the modern-day obstetrics. The aim of this study is to study the effectiveness of forceps delivery in modern obstetrics. Methods: In the present observational study, 20 cases of forceps delivery were studied for maternal and foetal outcomes including postpartum hemorrhage, perineal tears, Apgar score, NICU admissions, birth injury, and mortality. Results: The most common indication for forceps application was maternal exhaustion (80%) followed by foetal distress. All the cases of forceps application in the present study were associated uneventful vaginal delivery. No any adverse maternal outcomes including perineal tears, post-partum hemorrhage was observed in this study. Average birth weight in the present study was 3.2 kgs and Apgar scores at birth and five minutes was within normal limits. No any birth injury was noted in any of the newborns. Conclusions: Forceps delivery is a safe and effective option in modern day obstetrics to reduce the alarming rise in rates of caesarean section globally. Training should be encouraged to develop the expertise of this art of forceps delivery.